Prosecution, Conviction, and Deterrence in Child Maltreatment Cases - Gifford, Elizabeth J. (Criminal justice and behavior, 2017)
This study examines how decisions made by the criminal justice system in child maltreatment cases affect defendants’ future probability of committing a child maltreatment offense, another offense, or having a child involved in child protective services (CPS). A sample of parents who were arrested on a child maltreatment charge during 2005 to 2010 (N = 6,940) was drawn from North Carolina administrative records from the criminal court, birth certificates, and CPS. Instrumental variables included the prosecutor’s prosecution rate and the judge’s conviction rate. Rearrest rates for child maltreatment offenses were low (3%), but high for other offenses (43%), as were assessments by CPS (43%). Being prosecuted and convicted reduced probabilities of rearrest in some model specifications. However, prosecution only decreased the probability of rearrest for child maltreatment. Neither prosecution nor conviction prevented future CPS involvement, suggesting the need to better understand what supports can prevent adverse outcomes in this population.